마약류 중독자 예방 및 사회재활서비스 개발 위한 일본, 태국 사례와의 비교 - 백형의(Hyung-Ui Baik); 이송희(Song-Hee Lee); 이주용(Ju-Yong Lee) (한국콘텐츠학회 논문지, 24(3), 2024)
본 연구의 목적은 아시아를 중심으로 마약중독 정책 및 예방과 사회재활서비스를 살펴봄으로써 국내 적용할 수 있는 마약 중독 예방 및 사회재활서비스의 정책방향을 제시하고자 한다. 이를 위한 연구방법으로는 일본, 태국을 중심으로 마약류 중독자 정책 및 사회재활서비스 지원 사례에 대한 이론적 논의를 실시하고 최대유사체계분석기법(MSSD)을 활용하여 비교분석하고 국내 마약류 중독자 정책 및 사회재활서비스 모형 개발을 위한 시사점을 제시하였다. 연구결과 일본과 같이 치료와 재활 체계의 유기적 연결을 통한 마약류 사용자 재범 방지가 필요하며, 일본 약물남용대책추진본부 그리고 태국의 마약문제국가위원회와 같은 일원화된 정책추진기구 컨트롤 타워의 설립이 필요함을 제시하였으며 끝으로, 마약류 중독 예방, 치료와 사회재활 체계의 유기적인 연동을 통해 재범과 재발을 방지하고 단순사용자 등을 위한 전환 대책 개발이 필요함을 제안하였다. The purpose of this study is to suggest policy directions for drug addiction prevention and social rehabilitation services in Korea by examining drug addiction policies, prevention, and social rehabilitation services in Asia. As a research method, a theoretical discussion was conducted on the cases of drug addiction policies and social rehabilitation services in Japan and Thailand, and a comparative analysis was conducted through the most similar system design analysis method (MSSD). The implications for the development of Korean drug addiction policy and social rehabilitation service models were presented. The results showed that it is necessary to prevent recidivism of drug users by connecting treatment and rehabilitation systems like Japan. It is also necessary to establish a unified policy promotion organization, Control Tower, like Japan and Thailand. Finally, it was suggested that drug recidivism and relapse should be prevented by linking services at each stage of drug addiction prevention, treatment, and social rehabilitation. KCI Citation Count: 0